Currículos e o transtorno do déficit de atenção com hiperatividade (TDAH): práticas de produção e estratégias de governo de estudantes - Rhaissa de Alvarenga Coelho Martins (2020)
This dissertation is a study of the curricula - of two schools in Belo Horizonte (one of the municipal public network, which serves students mostly from the low-income classes but with the presence of middle-class students as well, and the other of the private network, who attend middle-class students) - do with students diagnosed with Attention Deficit Disorder (ADHD) and with those who are under suspicion of a diagnosis, since this group occupies a peripheral and conflicting place in legal devices, since there are no specific laws for them and it is the object of conflicts and disputes for senses in the different approaches to ADHD. In order to investigate how the curricula of the schools that house these students work, this study brings the results of research that articulated practices of postmodern educational ethnography and elements of Foucaultian genealogy to map and analyze the pedagogical practices prioritized, the government strategies that focus on these students, and the effects of ADHD's power on the curricula, students, teachers, and other professionals in the schools. ADHD is currently one of the disorders increasingly diagnosed in school-age individuals and implies, among other things, the medicalization, spatial separation, and differentiation of pedagogical practices aimed at these students. The research operates with concepts taken from Michel Foucault's studies and post-critical curriculum studies, especially concepts such as: curriculum, government, mode of subjectivation and norm. The argument developed here is that in the curricula of the schools researched three discourses operate mainly - the pedagogical discourse of the right to learning, the medical discourse, and the discourse of psychology - which, imbricated in power relations, make three power practices work - the practice of identification, the practice of diagnosis, and the practice of medicalization - to identify, diagnose, and medicalize the students read as deviant from the standards of normality established in society, so that they do not disturb the "pedagogy directed to the group" in course in the curricula in action of the schools. I show that this occurs in a very similar way in the two schools investigated and that they attend different social classes, even if the available school resources, the economic resources, the access to health systems, among other material and symbolic goods are differentiated. This dissertation shows the conflicts in the curriculum in action of the schools when teachers, due to the different pressures and demands to which they are submitted to teach all certain contents, are desperate to develop the official curriculum, so that the students diagnosed with ADHD follow the curricula already established and planned and that they consider they should implement. It also shows that forces such as educational legislation and the right to learning discourse, which pressure teachers to ensure that all students learn the same contents, at the same pace, making the normalization of the diagnosed children so that they can follow the official curriculum, are focused on the researched curricula. There is, however, resistance to this process. After all, this creates a conflict in the schools, causing teachers to be forced to build a separate curriculum for students diagnosed with ADHD.